The mystery of God : theology for knowing the unknowable - Boyer, Steven D., 1962-; Hall, Christopher A. (Christopher Alan), 1950- (Grand Rapids, MI : Baker Academic, 2012)
"How is it possible to do theology if the 'theos that we believe in is too great for human minds to take in? Christians have always known that God is a mystery and have developed strategies to aid believers in knowing him genuinely, but in a way that takes seriously the fact that he is beyond knowledge. Steven Boyer and Christopher Hall argue that the 'mystery of God' has a rightful place in theological discourse and contend that considering divine incomprehensibility invites reverence and humility on the believer's part. They investigate the biblical, historical, and practical foundations for understanding the mystery of God and examine its implications for a variety of theological issues and practices.The Mystery of God will serve as a supplemental text in college and seminary theology courses. It will also appeal to pastors and church leaders seeking intellectual and practical guidance for knowing the unknowable God" -- Publisher description.
Landscape on a sunny day -- Sun -- Meaning of mystery -- Necessity of mystery -- History of mystery -- Knowledge of mystery -- Landscape -- Mystery of the Trinity -- Mystery of the Incarnation -- Mystery and salvation -- Mystery and the life of prayer -- Mystery and world religions -- Seeking, finding, and seeking.
Includes bibliographical references and indexes.
Keywords: Mystery; God (Christianity); God (Christianity); Mystery